Measurement of Family-centered care perception and parental stress in a neonatal unit - Balbino, Flávia Simphronio (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2016)

(untitled) (Rev Lat Am Enfermagem)
OBJECTIVE: to evaluate the effects of the implementation of the Patient and Family-Centered Care Model on parents and healthcare perceptions and parental stress. METHOD: a quasi-experimental study developed in a neonatal unit of a university hospital in the municipality of São Paulo, Brazil, with the implementation of this model of care. Data collection were performed by two sample groups, one using non-equivalent groups of parents, and another using equivalent groups of healthcare professionals. The instruments Perceptions of Family-Centered Care-Parent Brazilian Version, Perceptions of Family-Centered Care-Staff Brazilian Version and Parental Stress Scale: Neonatal Intensive Care Unit, were applied to 132 parents of newborns hospitalized and to 57 professionals. RESULTS: there was a statistically significant improvement in the perceptions of the parents in most items assessed (p ≤0,05) and for the staff in relation to the family welcome in the neonatal unit (p = 0.041) and to the comprehension of the family's experience with the infant´s hospitalization (p = 0,050). There was a reduction in the average scores of parental stress, with a greater decrease in the Alteration in Parental Role from 4,2 to 3,8 (p = 0,048). CONCLUSION: the interventions improved the perceptions of parents and healthcare team related to patient and family-centered care and contributed to reducing parental stress.